The prognostic value of circulating microRNAs in heart failure. Issue 6 (June 2015) - Cakmak, Huseyin Altug; Coskunpinar, Ender; Ikitimur, Baris; Barman, Hasan Ali; Karadag, Bilgehan; Tiryakioglu, Necip Ozan; Kahraman, Kadriye; Vural, Vural Ali
<x xml:space="preserve">Abstract</x> Introduction Recent studies have demonstrated the potential of microRNAs (miRNA) as biomarkers in various cardiovascular disorders. The aim of the present study was to quantitatively evaluate the expression levels of miRNAs in patients with chronic congestive heart failure (CHF) in order to identify differential expression profiles as biomarkers with prognostic values. Materials and method The study included 20 clinically stable [New York Heart Association (NYHA) II] and 22 decompensated (NYHA III and IV) CHF patients and 15 healthy controls. miRNA profiling was performed using a microarray method. Dysregulated miRNAs were evaluated for their biomarker potential. Results Microarray profiling revealed an increase in the expression of miR-21, miR-650, miR-744*, miR-516-5p, miR-1292, miR-182, miR-1228, miR-595, miR-663b, miR-1296, miR-1825, miR-299-3p, miR-662 miR-122*, miR-3148 and miR-518e* and a decrease in the expression of miR-129-3p, miR-3155, miR-3175, miR-583, miR-568, miR-30d, miR-200a-star, miR-1979, miR-371-3p, miR-155-star and miR-502-5p in sera of CHF patients. The prognostic value of miR-182 [area under the curve (AUC) 0.695] was found to be superior to pro-brain type natriuretic peptide (NT-proBNP; AUC 0.350) and high-sensitivity C-reactive protein (hs-CRP) (AUC 0.475) by receiver operator characteristic (ROC) analysis. Cox regression analysis showed that miR-182 could predict cardiovascular mortality (P = 0.032). Conclusion We demonstrated the increased expression levels of circulating miRNAs in CHF as compared with controls. Moreover, miR-182 was found to be a potential prognostic marker in CHF.